Perceived coercion, perceived pressures and procedural justice arising from global lockdowns during the COVID-19 pandemic: A scoping review - Veronica Ranieri; Sunjeev K. Kamboj; Sarah J. L. Edwards (Public Library of Science (PLoS), 2023)
This aim of this scoping review is to map what is known about perceived coercion, perceived pressures and procedural justice within the context of the general population's experience of 'lockdowns' imposed by governments worldwide in response to the increased transmission of COVID-19. Arksey & O'Malley's (2005) framework for conducting scoping reviews was chosen. A sensitive search strategy was devised and conducted using PubMed, Scopus, and Web of Science using the following search terms: (adherence OR acceptance OR agreement OR trust OR distrust OR compliance OR willing*) OR (perceived coerc* OR percept* coerc* OR pressure OR force OR influence OR control OR threat OR justice) AND (lockdown) AND (COVID OR SARS-CoV-2 OR COVID-19). The database search initially produced 41,628 articles to screen. A total of 40 articles were included in this review and the following five themes were identified from the studies: perceived acceptability and willingness to adhere to lockdown; perceived control during lockdown; perceived pressures arising from lockdown; perceived threat of sanction from others and the procedural (in)justice of lockdown. Our synthesis suggests that i) individuals experienced an initial willingness and tolerance of lockdown that lessened over time as perceptions of personal control decreased; ii) that social influences may pressure individuals to follow or break lockdown rules; and iii) that justifiability and proportionality together with individuals' perceptions of harm from COVID-19 may impact the extent to which individuals adhere to lockdown. Furthermore, the review found an absence of information regarding specific individual characteristics and circumstances that increase the likelihood of experiencing perceived coercion and its related constructs and highlights a need for a better understanding of the cultural and socioeconomic factors affecting perceptions of, and adherence to, lockdown.